Super-dry reforming of methane intensifies CO2 utilization via Le Chatelier's principle - Buelens, Lukas C; Galvita, Vladimir V; Poelman, Hilde; Detavernier, Christophe; Marin, Guy B (Science (American Association for the Advancement of Science), 2016)
Efficient CO transformation from a waste product to a carbon source for chemicals and fuels will require reaction conditions that effect its reduction. We developed a "super-dry" CH reforming reaction for enhanced CO production from CH and CO We used Ni/MgAl O as a CH -reforming catalyst, Fe O /MgAl O as a solid oxygen carrier, and CaO/Al O as a CO sorbent. The isothermal coupling of these three different processes resulted in higher CO production as compared with that of conventional dry reforming, by avoiding back reactions with water. The reduction of iron oxide was intensified through CH conversion to syngas over Ni and CO extraction and storage as CaCO CO is then used for iron reoxidation and CO production, exploiting equilibrium shifts effected with inert gas sweeping (Le Chatelier's principle). Super-dry reforming uses up to three CO molecules per CH and offers a high CO space-time yield of 7.5 millimole CO per second per kilogram of iron at 1023 kelvin.